2020
DOI: 10.1101/2020.09.30.319962
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conserved human effector Treg signature is reflected in transcriptomic and epigenetic landscape

Abstract: Treg are critical regulators of immune homeostasis, and increasing evidence demonstrates that environment-driven Treg differentiation into effector (e)Treg is crucial for optimal functioning. However, human Treg programming under inflammatory conditions remains poorly understood. Here, we combine transcriptional and epigenetic profiling to identify the human eTreg core signature. Functional autoimmune inflammation-derived Treg display a unique transcriptional profile characterized by upregulation of both a cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…More recently, we studied the mechanism of human T regulatory (Treg) cells programming under inflammatory conditions. Using RegEnrich, we predicted a network of key regulators important for effector Treg differentiation, including the vitamin D receptor (VDR), which is further validated by H3K27ac and H3K4me1 ChIP-seq experiments 53 . These two independent experimental studies support that RegEnrich is able to accurately rank the key gene regulators that are mechanistically involved in immune cell development and functions.…”
Section: Discussionmentioning
confidence: 86%
“…More recently, we studied the mechanism of human T regulatory (Treg) cells programming under inflammatory conditions. Using RegEnrich, we predicted a network of key regulators important for effector Treg differentiation, including the vitamin D receptor (VDR), which is further validated by H3K27ac and H3K4me1 ChIP-seq experiments 53 . These two independent experimental studies support that RegEnrich is able to accurately rank the key gene regulators that are mechanistically involved in immune cell development and functions.…”
Section: Discussionmentioning
confidence: 86%
“…In this instance, they may be comparable to TIL-like cells in cancer settings, functionally overlapping with T EM . Interestingly overlap in phenotype and transcriptome has been demonstrated for inflamed joint- and tumor-derived Treg [ 69 ]. The transient expression of CD69 upon activation may be a gradient along which we can discern T RM from T EM , though TCR sequencing and single cell transcriptomics may provide a robust additional layer of characterization.…”
Section: Discussionmentioning
confidence: 99%
“…Tregs are a crucial part of suppressive immunity and have been shown to differ phenotypically and functionally in non-diseased and diseased states [ 60 , 68 , 69 , 70 ]. It has been shown that Tregs are part of the T RM compartment i.e., CD69-expressing Treg in synovial, uterus, and gut tissue [ 60 , 71 ].…”
Section: Recirculation Of Tissue–resident Memory T Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analogously, we found that FOXP3-induced Treg dysfunction was associated with DNA demethylation in specific regions which were enriched for AP-1 binding sites. AP-1 family members are thought to prepare sites for Foxp3 binding in Treg precursors (Samstein et al, 2012) and control the effector and tissuespecific Treg programs (DiSpirito et al, 2018;Mijnheer et al, 2020). On the other hand, Foxp3 opposes AP-1 activity by competing for binding with NFAT (Wu et al, 2006;Lee, Gao and Fang, 2008).…”
Section: Most Of Our Understanding Of the Role Ofmentioning
confidence: 99%